MANFAAT SIMPEDES BAGI KUPEDES PERIODE 2018 - 2020 - Riska Ervina, (2022)
Bank is a financial institution whose activities are to collect funds, distribute funds, and provide other financial services. BRI is one of the banks that prioritizes its services to grow and maintain market share in the micro segment or the lower middle class community, especially in micro, small and medium enterprises so as to be able to support the improvement of the community's economy. Most of the lower middle class people have difficulties in financing their business capital which is still limited and it is difficult to get capital assistance to develop their business. Bank BRI created the Rural General Credit (KUPEDES) product to help support the economy of rural communities. Therefore, the BRI bank needs a source of funds to be distributed to the public. In the third party fund, this micro segment is a savings product called Rural Savings (SIMPEDES) which has a large portion compared to others. With the increase in third party funds, banks can channel the collected funds into one of the bank's products, namely KUPEDES. The SIMPEDES savings fund plays an important role in the distribution of KUPEDES. From the results of interviews with five respondents who received KUPEDES, it is known that the business they are running is progressing and increasing so that it will increase income quite significantly and improve the welfare of the community.